The role of proteomics in progressing insights into plant secondary metabolism - Martínez-Esteso, María J.; Martínez-Márquez, Ascensión; Sellés-Marchart, Susana; Morante-Carriel, Jaime A.; Bru-Martínez, Roque (Frontiers in Plant Science, 2015)
The development of omics has enabled the genome-wide exploration of all kinds of biological processes at the molecular level. Almost every field of plant biology has been analysed at the genomic, transcriptomic and proteomic levels. Here we focus on the particular contribution of proteomic technologies to make progress in the knowledge and characterisation of plant secondary metabolism (SM) pathways since the early expectation created 15 years ago. We analysed how three major issues in the proteomic analysis of the plant secondary metabolism have been implemented in the different research works conducted. These issues are: (i) the selection of a suitable plant material rich in secondary metabolites of interest, such as specialised tissues and organs, and in vitro cell cultures; (ii) the proteomic strategy to access target proteins, either a comprehensive or a differential analysis; (iii) the proteomic approach, represented by the hypothesis-free discovery proteomics and the hypothesis-driven targeted proteomics. We also examine to what extent the most-advanced technologies have been incorporated into proteomic research in plant secondary metabolism and highlight some cutting edge techniques that would strongly benefit the progress made in this field.